REKONSTUKSI PERAN PERGURUAN TINGGI DALAM TRANSFORMASI PENDIDIKAN ISLAM DI INDONESIA - muhammad aril; Nabila Syahrani Muktar; Muhammad Arjun Saputra; Idrus Latif (PROGRAM STUDI PAI STIT TANGGAMUS, 2026)
This study examines the reconstruction of the role of higher education institutions in the transformation of Islamic education in Indonesia amidst globalization and rapid technological disruption. Islamic higher education institutions are required to adapt institutionally, academically, and technologically while maintaining their Islamic identity. The purpose of this research is to analyze how universities reconstruct their roles in supporting the transformation of Islamic education through curriculum innovation, integration of knowledge, and digitalization. This study employs a qualitative approach using literature review and document analysis from relevant academic sources, policies, and previous research findings. The results indicate that higher education institutions play a strategic role as agents of change by developing integrative curricula that combine Islamic studies with science and technology, strengthening digital learning infrastructure, and fostering interdisciplinary research. In addition, collaboration with various stakeholders such as pesantren, government, and industry enhances the relevance and quality of Islamic education. However, challenges such as limited human resources, institutional resistance, and technological gaps remain significant obstacles. In conclusion, the reconstruction of the role of higher education is essential to create adaptive, innovative, and competitive Islamic education. Sustainable policies, capacity building, and digital transformation are key factors in achieving effective and holistic educational transformation in Indonesia. Keywords: curriculum innovation, digital transformation, higher education, Islamic education, knowledge integration.